2022
DOI: 10.1039/d2tc01988d
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and high-resolution mechanical pressure sensing functions of mechanochromic fluorenylidene-acridane

Abstract: In the field of mechanochromic materials which respond to external stimulation, although observation of mechanochromism is an essential effort, numerical data almost have not been obtained. The quantitative mechanical pressure...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…This phenomenon is explained by the photophysical changes of FAs derived from ground-state mechanochromism. Further, in addition to the above mechanical pressure sensing, we found that FAs exhibit a response to alcohol 34 . An FA that has dimethoxy substituents on the fluorene unit could be returned from the blue color caused by mechanical pressure to its original yellow color by use of alcohol (Fig.…”
Section: Introductionmentioning
confidence: 53%
“…This phenomenon is explained by the photophysical changes of FAs derived from ground-state mechanochromism. Further, in addition to the above mechanical pressure sensing, we found that FAs exhibit a response to alcohol 34 . An FA that has dimethoxy substituents on the fluorene unit could be returned from the blue color caused by mechanical pressure to its original yellow color by use of alcohol (Fig.…”
Section: Introductionmentioning
confidence: 53%
“…To assess the response to mechanical pressure, we employed diffuse reflectance UV–vis spectroscopy (Figures b, S7b, and S8b). Focusing on the peak in the 500–600 nm wavelength range, which includes green and yellow, we observed a decrease in the peak height of the reflectance value with increasing mechanical pressure. Thus, we generated a calibration curve for the relationship between the mechanical pressure and the peak height of the reflectance value.…”
Section: Resultsmentioning
confidence: 99%
“…Among the FA derivatives in previous reports, FA, which prefers the folded conformer due to the electron-donating methoxy group, was employed. , FA was synthesized in six steps using commercially available materials. In the final step, FA was obtained by the Barton–Kellogg reaction using diazofluorenylidene and thioacridane (Scheme S1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following are the previous studies on color change according to the state of an object: When a mechanochromic fluorenylidene-acridane film generated by vacuum evaporation is mechanically stimulated, the molecular structure is deformed, and the film changes color from yellow to green [6]. Perovskite nanosheet hydrogels with mechanochromic structural colors instantly change from longwavelength orange to short-wavelength blue when a force is applied [7].…”
Section: Introductionmentioning
confidence: 99%